Optimalisasi Pemanfaatan Teknologi untuk Meningkatkan Kualitas Proses Pembelajaran di Kelas - Rahim, Abdul; Elsoin, Wensislaus Yulius; Bhia, Vinsensius Isodorus; Derian, Christian; Quevara, Ernesto Ce (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2024)
The use of technology in the learning process has become an important need to improve the quality of education in the digital era. This service activity aims to integrate technology in learning to improve the basic literacy skills of Buti Merauke State Middle School students. The method used includes three main stages: planning, implementation and evaluation. The planning stage is carried out through observation to understand student needs and design appropriate technology-based learning strategies. At the implementation stage, students are actively involved through the use of digital devices and interactive learning applications that support collaboration. Evaluation is carried out by observing the learning process and collecting feedback from participants to measure the effectiveness of the program. The results show that the use of technology is successful in increasing student engagement, basic literacy skills, and learning management efficiency. Although there are obstacles such as limited access to devices, this is overcome by teacher training and the provision of shared devices. This dedication proves that technology, if used strategically, can support inclusive and relevant learning.